Representación del concepto salud- enfermedad para los adolescentes: comportamientos y actitudes frente a las enfermedades de transmisión sexual - Uribe-S., Carlos M. (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Purpose of this article is to present result of a qualitative study about the concept that teen-agers do have about health and disease. The main topic was the sexual transmission diseases (SW), since teenagers are showing sexual activity at younger ages. Twenty five volunteer teenagers from Rionegro (Antioquia) were included in the study, through an interview. They all had some sexual experience. Study showed that although teenager may now about risks of STD, they develop different attitudes and behavior after the first STD is suffered: some of them develop a feeling of "status" in their group. Some other think of using their disease a revenge because they were infected. A third group use STD as a way to generate pity, and get protection. There is also a group resignate to the fact of being sick. Teenagers are worried for loneliness and being rejected, and because of these, they develop attitudes and feelings that affect their quality off life, and their social relation. There are included several important ideas for the construction of Heath - Disease Process.